Pemahaman Guru Pendidikan Agama Katolik (PAK) terhadap Ajaran Moral pada Jenjang SMA di Pontianak - Gustaf Hariyanto; Andreas Muhrotien; Mayong Andreas Acin (Jurnal Penelitian Pendidikan Agama Katolik, 2022)
Various scholars argue that there is a close relationship between education with moral teachings and education with religion on the other hand. People in previous decades believed that the essence of all education lies in moral and religious strength. Morality is closely related to human behavior from a normative perspective. For example, what should be done is different from what is done. Apart from we ourselves, morality is also concerned with actions that affect the interests and happiness of others. However, these moral claims must be addressed and accepted critically. There must be a fundamental and critical understanding of why someone should act according to specific provisions. In this case, an understanding of the concept of morality is needed. The research aims to determine the understanding of Catholic religious teachers at the high school level regarding the relationship between moral and religious teachings. Aspects that want to be known include how the basic and critical understanding of religious teachers – in the form of a fundamental orientation – in accounting for moral views rationally. The method used in this research is qualitative. In addition to interviews and questionnaires, the Focus Group Discussion technique was also used in this study. This research shows that the teacher’s understanding of moral and religious teachings is dynamic, whole, and holistic. The research’s findings show that most Catholic teachers view moral teachings as the same as religious teachings, both material and form.